Male subfertility and the risk of major birth defects in children born after in vitro fertilization and intracytoplasmic sperm injection: a retrospective cohort study - Seung Chik Jwa; Junna Jwa; Akira Kuwahara; Minoru Irahara; Osamu Ishihara; Hidekazu Saito (BMC, 2019)
Abstract Background Children born after intracytoplasmic sperm injection (ICSI) are at increased risk of specific major birth defects compared with children born after in vitro fertilization (IVF). However, whether this risk is due to the treatment itself (i.e., IVF or ICSI) or underlying male subfertility is unknown. This study investigated the associations between male subfertility and the risk of major birth defects in children born after IVF and ICSI. Methods We conducted a retrospective cohort study using data from the Japanese assisted reproductive technology registry between 2007 and 2014. Fresh embryo transfer cycles registered from 2007 to 2014 that resulted in singleton live births, still births, or selective terminations were included (n = 59,971). Major birth defects were defined by the US Centers for Disease Control and Prevention guidelines, excluding chromosomal abnormalities. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using generalized estimating equations adjusting for potential confounders. Results Major birth defects were reported in 626/59,971 (1.04%) cases. Among IVF cycles, male subfertility was associated with significantly greater risks of hypospadias (3/3163 [0.09%] vs 4/28,671 [0.01%], adjusted OR = 6.85, 95% CI 2.05-22.9, P = 0.002) and atrial septal defects (4/3163 [0.13%] vs 9/28,671 [0.03%], adjusted OR = 3.98, 95% CI 1.12-14.1, P = 0.03) compared with fertile men. Subgroup analysis using sperm parameters showed that oligozoospermia (i.e., sperm concentrations < 15 million/mL) was significantly associated with a greater risk of ventricular septal defects compared with normal sperm concentrations in IVF pregnancies (5/868 [0.58%] vs 60/28,090 [0.21%], adjusted OR = 2.68, 95% CI 1.15-6.27, P = 0.02), and severe oligozoospermia (i.e., sperm concentrations < 5 million/mL) was significantly associated with an increased risk of hypospadias compared with normal sperm concentrations in ICSI pregnancies (5/3136 [0.16%] vs 5/16,865 [0.03%], adjusted OR = 3.88, 95% CI 1.14-13.2, P = 0.03). Conclusions The results of this exploratory study suggest that underlying male subfertility may play a role in the risk of major birth defects related to ICSI and IVF. Further research, including systematic reviews adjusting for confounders, is required to confirm the associations between male subfertility and major cardiac and urogenital birth defects.